Laws in the hospitality industry : the Philippine tourism laws simplified - Cagurangan, Tranquilino R. Jr. (Manila, Philippines : Mindshapers Co. Inc., 2017)
This book is intended for college students and professionals in the tourism and hospitality management industry.
Chapter I : Introduction to tourism laws -- Chapter II : Constitutional provisions relative to tourism establishments -- Chapter III : The Laws on obligations and contracts -- Chapter IV : Laws on sales -- Chapter V : Law on partnership and corporation -- Chapter VI : The Law on common carrier and the air passenger bill of rights -- Chapter VII : Labor laws and management in the tourism establishments-- Chapter VIII : Accreditation of hotels and other tourism establishments in the Philippines and the tourism act of 2009.
Includes bibliographical references.
Keywords: TOURIST TRADE -- LAW AND LEGISLATION -- PHILIPPINES